Characterization of tip size and geometry of the pipettes used in scanning ion conductance microscopy. (April 2016) - Tognoni, Elisabetta; Baschieri, Paolo; Ascoli, Cesare; Pellegrini, Monica; Pellegrino, Mario
Highlights: Several methods for characterizing SICM probe size and geometry are described. Imaging methods provide more information at the cost of a more complicated setup. Less expensive methods rely on the measurement of a parameter related to tip size. The method to be preferred depends on the actual experimental problem. Abstract: Scanning ion-conductance microscopy (SICM) belongs to the family of scanning-probe microscopies. The spatial resolution of these techniques is limited by the size of the probe. In SICM the probe is a pipette, obtained by heating and pulling a glass capillary tubing. The size of the pipette tip is therefore an important parameter in SICM experiments. However, the characterization of the tip is not a consolidated routine in SICM experimental practice. In addition, potential and limitations of the different methods available for this characterization may not be known to all users. We present an overview of different methods for characterizing size and geometry of the pipette tip, with the aim of collecting and facilitating the use of several pieces of information appeared in the literature in a wide interval of time under different disciplines. In fact, several methods that have been developed for pipettes used in cell physiology can be also fruitfully employed in the characterization of the SICM probes. The overview includes imaging techniques, such as scanning electron microscopy and atomic Force microscopy, and indirect methods, which measure some physical parameter related to the size of the pipette. Examples of these parameters are the electrical resistance of the pipette filled with a saline solution and the surface tension at the pipette tip. We discuss advantages and drawbacks of the methods, which may be helpful in answering a wide range of experimental questions.